The Select Seminar Process: A Program that Works - Nelson Armin; Richard Bamberger; Richard McDonald (Educational Considerations, 1989)
Select seminars follow a very simple structure based upon a set of guiding principles. (Program Approaches to Administrative Training and Development.)